2013
DOI: 10.1017/s1368980013002127
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural differences in adolescent eating behaviour: a multilevel cross-sectional study of 15-year-olds in Scotland

Abstract: Objective: Improving the diet of the Scottish population has been a government focus in recent years. Population health is known to vary between geographies; therefore alongside trends and socio-economic inequalities in eating behaviour, geographic differences should also be monitored. Design: Eating behaviour data from the 2010 Scotland Health Behaviour in School-aged Children survey were modelled using multilevel linear and logistic modelling. Setting: Data were collected in schools across urban and rural Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
2
32
0
1
Order By: Relevance
“…In the urban environment, meat and fish were eaten more regularly during the week. Studies have shown that children and adolescents, especially those from urban areas and those with greater economic resources, consume excessive amounts of protein, particularly meat [11], as confirmed in this study.…”
Section: A) Analysis Of Eating Habitssupporting
confidence: 84%
See 2 more Smart Citations
“…In the urban environment, meat and fish were eaten more regularly during the week. Studies have shown that children and adolescents, especially those from urban areas and those with greater economic resources, consume excessive amounts of protein, particularly meat [11], as confirmed in this study.…”
Section: A) Analysis Of Eating Habitssupporting
confidence: 84%
“…Despite the differences between the rural and urban environments with regard to eating habits, it was shown that adolescents who were overweight/obese do not have different eating habits from those who have a normal weight [11].…”
Section: A) Analysis Of Eating Habitsmentioning
confidence: 98%
See 1 more Smart Citation
“…Breakfast skipping has also been found to be more common in urban compared to suburban and rural children in the US . In Scotland, rural students had more healthful behaviours (increased vegetable consumption and decreased sweets and crisps consumption); possibly due to growing their own vegetables and having few shops to purchase snacks from on the route home from school …”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, some secondary schools prohibit first year pupils from leaving school premises at lunchtime (Scotcen, 2011). Pupils attending schools in more rural areas perhaps have less opportunity to visit local retailers at lunchtime, and evidence suggests that teenagers living in rural areas of Scotland eat a diet more in line with recommendations than those living in urban areas (Levin, 2013). …”
Section: Introductionmentioning
confidence: 99%